THE RESURRECTION OF SCHIZOSTACHYUM BIFLORUM McCLURE (BAMBUSOIDEAE) - Furqon Al Muzakki; Tatik Chikmawati; Alex Hartana (Research Center for Biology, 2020)
MUZAKKI, F. A., CHIKMAWATI, T. & HARTANA, A. 2020. The resurrection of Schizostachyum biflorum McClure (Bambusoideae). Reinwardtia 19(2): 93‒96. ‒‒ Based on newly collected specimens from Mount Salak referable to Schizostachyum biflorum, made it justifiable to recognize this species as different from S. iraten Steud., to which formerly it was synonymized. A complete description of S. biflorum, a comparative tabulation of the morphological features that distinguished it from S. iraten, and figures of the two species are presented.